Food Components and the Immune System: From Tonic Agents to Allergens - Faria, Ana Maria C.; Gomes-Santos, Ana Cristina; Goncalves, Juliana L.; Moreira, Thais G.; Medeiros, Samara R.; Dourado, Luana P.; Cara, Denise C. (Frontiers in Immunology, 2013)
The intestinal mucosa is the major site of contact with antigens, and it lodges the largest lymphoid tissue in the body. In physiological conditions, microbiota and dietary antigens are the natural sources of stimulation for the gut associated lymphoid tissues (GALT) and for the immune system as a whole. Germ free models have provided some insights on the immunological role of gut antigens. However, most of the GALT is not located in the large intestine, where gut microbiota is prominent. It is concentrated in the small intestine where protein absorption takes place. In this review, we will address the involvement of food components in the development and the function of the immune system. Studies in mice have already shown that dietary proteins are critical elements for the developmental shift of the immature neonatal immune profile into a fully developed immune system. The immunological effects of other food components (such as vitamins and lipids) will also be addressed. Most of the cells in the GALT are activated and local proinflammatory mediators are abundant. Regulatory elements are known to provide a delicate yet robust balance that keeps the gut homeostasis at check. Usually antigenic contact in the gut induces two major immune responses, oral tolerance and production of secretory IgA. However, under pathological conditions mucosal homeostasis is disturbed resulting in inflammatory reactions such as food hypersensitivity. Food allergy development depends on many factors such as genetic predisposition, biochemical features of allergens and a growing array of environmental elements. Neuroimmune interactions are also implicated in food allergy and they are examples of the high complexity of the phenomenon. Recent findings on the gut circuits triggered by food components will be reviewed to show that, far beyond their role as nutrients, they are critical players in the operation of immune system in health and disease.